Gradient Trigger Mechanisms Related to Bistability Regimes in a Leech Heartbeat Model - Guan, Y.Zh; Liu, Sh.Q.; Zeng, Y.J. (Нейрофизиология, 2014)
We studied bursting patterns underlied by bifurcation phenomena and chaotic spiking in a computational leech heartbeat model. We observed the gradient physical properties of the ISI trains and amplitude (shift of the membrane potential) when the parameter gleak was mildly changed and found different bistable areas. The resulting computation implies that (i) classification of the intensity of the input information is feasible in this regime, (ii) a neuron’s working level can be marked by its range in a typical bifurcation, and (iii) there are invisible triggers underlying subtle mechanisms in the model.